7-Amino-4-methylcoumarin as a fluorescent substitute for Schiff's reagent: a new method that can be combined with hemalum and eosin staining on the same tissue section. (2nd January 2023) - Takase, Hiroshi; Murase, Takayuki; Hachisuka, Daisuke; Sakamoto, Yuma; Sugiura, Mariko; Nakano, Satsuki; Fujii, Keiichiro; Masaki, Ayako; Inagaki, Hiroshi
ABSTRACT: An aqueous 7-amino-4-methylcoumarin (AMC) solution exhibits strong fluorescence under ultraviolet (UV) light and can be used as a Schiff reagent to visualize aldehydes. We investigated hemalum and eosin (H & E) and AMC staining for histological and pathological analysis. Sections of normal and lesioned human tissues were stained with combined H & E/AMC staining. After H & E/AMC staining, the H & E morphology was preserved under bright field microscopy. The AMC fluorescent signals observed under UV light were intense and the staining pattern was identical to that obtained by periodic acid-Schiff (PAS) staining. AMC staining of archived H & E sections also was successful. Diastase digestion differentiated glycogen from other AMC positive elements. Using H & E/AMC staining, mucus-rich adenocarcinoma cells, amebic trophozoites and fungal hyphae were visualized clearly under UV excitation. Using H & E/AMC staining, H & E and PAS-like histological imaging can be obtained using a single tissue section. H & E/AMC is useful for pathologic diagnosis especially when information from PAS staining is critical, the number of tissue sections is limited and/or the lesion in question is small.